2021
DOI: 10.1029/2021gl094719
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic as a Trigger for Pacific‐Wide Decadal Climate Change

Abstract: The Interdecadal Pacific Oscillation (IPO) (Power et al., 1999), also called the Pacific Decadal Oscillation (Mantua et al., 1997;Zhang et al., 1997), is a pan-Pacific dominant mode of decadal climate variability, characterized by a tripolar pattern with one-sign SST anomalies in the tropical Pacific and opposite-sign SST anomalies in the western-central regions of North and South Pacific. Its Atlantic counterpart, the Atlantic Multidecadal Variability (AMV) (Ruprich-Robert et al., 2017), which is generally re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 54 publications
(81 reference statements)
3
25
0
Order By: Relevance
“…The teleconnection by AMO is the origination for the physical processes discussed in the present study. Previous studies have shown that the AMO‐like forcing could induce pressure, wind and air‐sea heat flux anomalies in the North Pacific Ocean and then drive the oceanic environment changes (e.g., Gong et al., 2020; Sun et al., 2017; L. Wu et al., 2008; Yao et al., 2021; Zhang & Delworth, 2007). The possible mechanism for this interbasin teleconnections is through the atmospheric bridge (Li et al., 2016; Meehl et al., 2021; Z. Zhang et al., 2018).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The teleconnection by AMO is the origination for the physical processes discussed in the present study. Previous studies have shown that the AMO‐like forcing could induce pressure, wind and air‐sea heat flux anomalies in the North Pacific Ocean and then drive the oceanic environment changes (e.g., Gong et al., 2020; Sun et al., 2017; L. Wu et al., 2008; Yao et al., 2021; Zhang & Delworth, 2007). The possible mechanism for this interbasin teleconnections is through the atmospheric bridge (Li et al., 2016; Meehl et al., 2021; Z. Zhang et al., 2018).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…(a) The AMV can modulate the North Pacific Subtropical High (Lyu et al., 2017), which in turn leads to wind anomalies along the NPMM region and influences SST there (Yu et al., 2015). (b) The AMV modulates the Pacific Walker Circulation and trade winds along the equatorial Pacific (Kucharski et al., 2016; McGregor et al., 2014; Meehl, Hu, et al., 2021; Ruprich‐Robert et al., 2017; Yao et al., 2021), which generates thermocline adjustments for developing the IPV (Li et al., 2016). Thus, there is a possibility that the AMV can provide additional skill for IPV decadal prediction.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown the AMV modulations on the IPV (Dong et al., 2006; Kucharski et al., 2016; Li et al., 2016; McGregor et al., 2014; Meehl, Hu, et al., 2021; Ruprich‐Robert et al., 2017; Yao et al., 2021), but its importance on IPV decadal prediction remains unclear. Chikamoto et al.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations